Phūminām Čhangwat Nakh̨ōn Sawan - Wichīan ʻAchinōbunyawat (Khrōngkān Sưksā Khonkhwā Wičhai thāng Watthanatham, Sahawitthayālai Phutthachinnarāt : Sūn Sinlapawatthanatham, Witthayālai Khrū Nakh̨ōn Sawan, 1994)
Study on place names in Nakhon Sawan Province, Thailand.